Interpretation of Qur'anic Economics Using a Thematic Interpretation Approach in Overcoming Increasing Social and Economic Inequalities in Indonesia - Mukhtar Yunus (Journal AGENCY, 2024)
To address the widening socio-economic disparity in Indonesia in 2024, this study examines the economic interpretation of the Qur'an using thematic exegesis techniques. Qur'anic verses related to ownership, wealth distribution, zakat, infaq, almsgiving (sedekah), and the prohibition of usury (riba) and monopolistic behavior are comprehensively analyzed through a qualitative research method with a thematic interpretation approach. Secondary data for the 2024 period are sourced from recent scientific literature, the Indonesian Central Bureau of Statistics (BPS), Bank Indonesia, and the Ministry of Finance, alongside textual analyses of the Qur'an and Hadith. The research findings indicate that Indonesia's economic disparity increased significantly in 2024, with the Gini coefficient rising to 0.384 and the expenditure ratio between the top 20% wealthiest population and the bottom 40% poorest population climbing to 2.37. Based on the thematic exegesis approach, the Qur'anic economic concept emphasizes distributive justice, poverty reduction, and public economic empowerment through the instruments of zakat, infaq, almsgiving, and waqf (ZISWAF). This study concludes that mitigating socio-economic disparity and achieving equitable wealth distribution in Indonesia can be realized through the systematic implementation of Qur'anic economic principles within fair fiscal and monetary policies.